Unveiling the Relationship Between Anxiety and Self-Esteem in Adult Populations - Sangeeta Kakkar; Harkirat Singh (International Journal of Children, 2025)
The purpose of this study was to investigate the intricate connection between anxiety and self-esteem in adult Delhi National Capital Region (NCR) residents. A purposive sample approach was employed to select seventy people from this region. The study measured participants' self-worth and gathered pertinent background data using the Rosenberg Self-Esteem Scale (RSES) and a sociodemographic data form. In the data analysis, a t-test was employed to assess significant differences between variables. Furthermore, the Hamilton Anxiety Scale (HAM-A) validity and reliability were assessed using two different populations. The initial sample, comprising 97 individuals with anxiety disorders, enabled a targeted evaluation of the scale's capacity to distinguish between different anxiety levels. The results highlighted the significance of treating individual variability in mental health disorders by revealing significant variations in participants' anxiety levels. The results of this study have greatly increased awareness of adult anxiety and depression symptoms, especially in cities like Delhi NCR. This study adds to the expanding body of information on mental health by demonstrating the relationship between anxiety and self-esteem. The findings can guide therapies and policies targeted at enhancing individuals' psychological health. These findings underscore the complex psychological interplay between anxiety and self-esteem among adults living in urban settings such as Delhi NCR. The study further emphasizes the influence of environmental pressures, lifestyle factors, and social expectations on emotional well-being. By identifying the interdependent nature of these variables, the research promotes a deeper understanding of how self-perception impacts anxiety management and overall quality of life, highlighting the importance of early interventions and supportive mental health strategies.
Keywords: Adult mental health; Anxiety; and delhi NCR; psychological well-being; self-esteem